Boiler water treatment : principles and practice. - Frayne, Colin, ....- (New York : Chemical publishing, 2002)
This two-volume work provides practical boiler plant information, covering all types of boiler systems, including those used in residential complexes, commercial and institutional buildings, and industrial facilities. All types of boiler plants are discussed, from small cast iron units to large utility and nuclear power plants. Although the reference is primarily concerned with applied chemistry, initial chapters in Volume I present basic engineering concepts. Subjects discussed include fluid dynamics, thermodynamics, types and designs of boilers, and the function of all critical system auxiliaries and components. Volume II covers boiler maintenance and troubleshooting, fuel treatments, combustion gas analysis, pre- treatment processes, chemicals, and operational management, as well as historical and modern program design and control in accordance with international standards. The book is useful for boiler plant owners and operators.
2: Treatments, program design, and management.